Effects of Physiotherapy Care in the Postoperative of Total Hip Arthroplasty: An Integrative Review - Sales, Weslley Barbosa; Costa, Rômulo Claudino Sales e Rodrigues; Silva, José Vinicius Bulhões da (Journal of Sports Medicine and Therapy, 2024)
Introduction: Total hip arthroplasty is a procedure widely performed in orthopedics, as it is capable of restoring function in the hips, severely affected by orthopedic diseases, such as osteoarthritis and consequently reducing pain and restoring function. Objective: To identify the effects of physical therapy in the postoperative period of total hip arthroplasty. Method: This is an integrative review, of an exploratory and descriptive nature, carried out between January and May 2024 and guided by the recommendations of the Joanna Brigs Institute. The Pubmed, LILACS, and SciELO databases were used. The following descriptors were used for the search procedure: “Physiotherapy and hip arthroplasty”. For the operationalization of the search, the Boolean descriptor “AND” was used to cross the descriptors. Articles were included in randomized clinical trials, published in full, without restriction of language and/or year of publication, which dealt with the theme addressed and that responded to the objective of the study. On the other hand, editorial letters, any type of literature review, articles unavailable at the time of search, abstracts and/or full articles published in annals of scientific events, preprints, and articles without abstracts were excluded. Results: After searches in the databases, 108 articles were identified on the platforms, subsequently, all had their titles and abstracts read, then 58 articles were excluded for not meeting the eligibility criteria, leaving 50 articles carefully read in full, after complete reading, only 7 articles composed the final sample. Final considerations: based on the reading and analysis of the articles that were previously selected, it was observed that there is no pre-established protocol among the authors for the postoperative period of hip arthroplasty, but that physical therapy techniques associated with therapist support and an early start are responsible for improving functionality, quality of life, pain reduction and increased muscle strength.